Effect of carboxymethylcellulose and xanthan gum on the physicochemical and sensory properties of passion fruit topping sauces - Boonditsataporn, L.; Vatthanakul, S. (International Journal of Agricultural Technology, 2022)
In food industry, hydrocolloid is the food additive that widely used in food product as a stabilizer, thickener, emulsifier, or gelling agent for improve the properties of food products. Over the last year, the food industry has begun to apply more than one type of hydrocolloid into food products to obtain benefits in various fields, whether used to develop a formula, enhance nutrition, enhance values, or reduce production costs. This research studied on effect of use of some hydrocolloids alone or in combinations on the quality of passion fruit topping sauces that was acceptable to consumers. The research determined the effects of carboxymethylcellulose (CMC) and xanthan gum in various ratios (1.00:0.00, 0.75:0.25, 0.50:0.50, 0.25:0.75 and 0.00:1.00) on the quality of passion fruit topping sauces. The result showed that increasing the ratio of xanthan gum and decreasing the ratio of CMC tended to increased the appearant viscosity, firmness, consistency, index of viscosity, and color parameter (L*, a* and b*) of passion fruit topping sauce, but decreased in pH values. In terms of sensory, from the quantitative descriptive analysis showed that increasing the ratio of xanthan gum resulting in increased intensity score of viscosity in mouthfeel and decreased intensity score of passion fruit flavor, and smoothness of passion fruit topping sauce. In addition, the consumer preference test founded that ratio of CMC and xanthan gum at 0.50:0.50 had a highest overall liking score and just about right in terms of viscosity of passion fruit topping sauce. In general, these hydrocolloids gave a good quality of topping sauces in terms of texture properties when they were used with combinations rather than being used individually. The using of CMC combination with xanthan gum would be the interesting ingredient for improvement viscosity and consistency of the topping sauce product or other sauce products